The Impact of The Decision of the Constitutional Court Number 91/puu-xviii/2020 on The Establishment of Regional Regulations Concerning Levies Building Approval - Satria Adhitama Sukma; Fitriani Ahlan Sjarif (IHSA Institute, 2022)
Government Regulation Number 16 of 2021 concerning Implementing Regulations of Law Number 28 of 2002 concerning Buildings orders the establishment of a Regional Regulation concerning Retribution for Building Approval within a period of 6 (six) months. Before all Regional Governments had time to form a Regional Regulation on Building Approval Levy, the Constitutional Court issued Decision Number 91/PUU-XVIII/2020 on the Review of Law Number 11 of 2020 concerning Job Creation. The decision does not justify the establishment of implementing regulations of Law Number 11 of 2020 concerning Job Creation for 2 years until the law is finish repaired. So, what is the impact of the Constitutional Court's Decision Number 91/PUU-XVIII/2020 on the formation of Regional Regulations concerning Retribution for Building Approval? How does the Ministry of Home Affairs see the problem of the Regional Government that has not yet formed a Regional Regulation on Retribution for Building Approval? How are the Policy Regulations that have been issued by the Ministry of Home Affairs seen from the Science of Legislation? Through the normative juridical method, it was concluded that the Constitutional Court's decision caused new turmoil for the Regional Government which at that time was still adapting to the new system. The Ministry of Home Affairs then issued Instruction Number 68 of 2021 which ordered the Regional Government to continue the process of forming a regional regulation implementing the Job Creation Law. However, after that, the Minister of Home Affairs along with 3 other Ministers actually issued a Circular Letter which actually extended the time period for the formation of the Regional Regulation concerning Retribution for Building Approval until 2024. From a legal perspective, about Instruction Number 68 of 2021 seems to be interpreted as a follow-up to the Decision of the Constitutional Court Number 91/PUU-XVIII/2020, although there are also policy regulations in the form of a Joint Circular of 4 Ministers provide a time limit who different from Government Regulation Number 16 of 2021 concerning Implementing Regulations of Law Number 28 of 2002 concerning Buildings.